The diasporic canon: American anthologies of contemporary Italian poetry, 1945-2015 - Arnaldi, M (2019)
This thesis offers the first history of contemporary Italian poetry in the United States from the end of the Second World War to the present. It traces the forms of reception and translation of Italian lyric by concentrating on one of the most powerful instruments of cultural dissemination: the poetry anthology. By combining a supra-national with a transdisciplinary approach, it defines the Italian canon in America as diasporic: first, because it was created by migrants and political refugees; second, because it promoted marginal groups such as the avant-garde, women poets and dialect poets; and third, because it constructed a hybrid culture, half-American and half-Italian, that expressed itself through different forms of translation (bilingual, trilingual, multilingual and visual). The result is the creation of an inverted, almost mystifying canon, one that has been built upon historical anticipations of later developments in Italy, transcontinental influences, but also distortions and even errors. Neither an anti- nor a counter-canon, the diasporic tradition analysed here does not compete with, or oppose, its Italian equivalent; rather, it complements and illuminates it by giving it a new transcultural dimension. By exploring Italian poetry’s potential for mobility and transformation, this thesis contributes an original viewpoint to existing narratives of diaspora and migration, both within and outside the fields of Italian, American, and Italian-American Studies. It also puts forward a renewed image of literature in translation and of its significance, whilst problematising received notions of nationality, ethnicity, gender, genre, and authorship.